The determinants of full-service carriers airfares in European hub-to-hub markets - Zhang, Shengrun; Derudder, Ben; Witlox, Frank (European Journal of Transport and Infrastructure Research, 2014)
This paper explores the factors influencing the pricing behaviour of full-service carriers in European hub-to-hub markets. Drawing on a 2009 dataset containing route and airfare information, we establish an econometric model to estimate the impact of route structure, alliances, and market concentration on the pricing of European full-service carriers in these markets. The results suggest that alliances on routes connecting two primary hubs, airport concentration, market share inequality and competition from low-cost carriers influence average airfares of full-service carriers in the European hub-to-hub markets.